Formulation and Antioxidant Activity of Clay Mask of Tomato (Solanum lycopersicum L.) Lycopene Extract with Variation of Concentration of Kaoline and Bentonite Bases): Formulasi dan Aktivitas Antioksidan Masker Clay Ekstrak Likopen Tomat (Solanum lycopersicum L.) dengan Variasi Konsentrasi Basis Kaolin dan Bentonit - Syamsidi, Armini; Syamsuddin, Alifah Magfirah; Sulastri, Evi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Free radicals can cause damage to human skin, so antioxidants are needed to counteract the negative effects of these free radicals, for example preparations in the form of face masks. Tomatoes (Solanum lycopersicum L.) contains nutritious substances, namely lycopene which can be useful as an antioxidant for the skin. This study aims to determine the effect of variations in kaolin and bentonite bases on physical characteristics and antioxidant activity of tomato lycopene extract clay mask, and to determine the best formula. Tomato lycopene extract was modified into a microemulsion preparation to maintain the stability of antioxidant activity. Kaolin and bentonite used as bases had various concentrations in each formula, namely F1: 15% and 2%, F2: 20% and 1.5%, F3: 25% and 1%, F4: 30% and 0.5%. The results showed that the four clay mask preparations were homogeneous and no change in color, shape and aroma. The pH test on the four formulas was F1: 4.33 ± 0.35, F2: 5.58 ± 0.24, F3: 6.48 ± 0.22, and F4: 7.34 ± 0.08. The viscosity test on the four formulas was F1 : 20213.3 ± 140.4, F2: 24133.3 ± 83.26, F3 29080 ± 105.83, F4 33293.3 ± 378.06. The spreadability test was F1 6.59 ± 0.24, F2 5.59 ± 0.16, F3 4.85 ± 0.11, F4 7.84 ± 0.05. The test time for the preparation to dry was F1 19.02 ± 0.36, F2 15.33 ± 0.54, F3 11.27 ± 0.42, F4 8.24 ± 0.50. F1 and F2 are very easy to clean. Meanwhile, F3 and F4 are easy to clean. The best formula for clay masks is the F3 preparation where the concentration of kaolin is 25% and bentonite is 1%. It also showed the lower antioxidant activity (741.34 µg/mL) than other formulas.